Evaluation of the stability of the stereotactic Leksell Frame G in Gamma Knife radiosurgery. (8th May 2016) - Rojas‐Villabona, Alvaro; Miszkiel, Katherine; Kitchen, Neil; Jäger, Rolf; Paddick, Ian
Abstract : The purpose of this study was to evaluate the stability of the Leksell Frame G in Gamma Knife radiosurgery (GKR). Forty patients undergoing GKR underwent pretreatment stereotactic MRI for GKR planning and stereotactic CT immediately after GKR. The stereotactic coordinates of four anatomical landmarks (cochlear apertures and the summits of the anterior post of the superior semicircular canals, bilaterally) were measured by two evaluators on two separate occasions in the pretreatment MRI and post‐treatment CT scans and the absolute distance between the observations is reported. The measurement method was validated with an independent group of patients who underwent both stereotactic MRI and CT imaging before treatment (negative controls; n: 5). Patients undergoing GKR for arteriovenous malformations (AVM) also underwent digital subtraction angiography (DSA), which could result in extra stresses on the frame. The distance between landmark localization in the scans for the negative control group (0.63 mm; 95% CI: 0.57–0.70; SD: 0.29) represents the overall consistency of the evaluation method and provides an estimate of the minimum displacement that could be detected by the study. Two patients in the study group had the fiducial indicator box accidentally misplaced at post‐treatment CT scanning. This simulated the scenario of a frame displacement, and these cases were used as positive controls to demonstrate that the evaluation method is capable of detecting a discrepancy between the MRI and CT scans, if there was one. The mean distance between the location of the landmarks in the pretreatment MRI and post‐treatment CT scans for the study group was 0.71 mm (95% CI: 0.68–0.74; SD:0.32), which was not statistically different from the overall uncertainty of the evaluation method observed in the negative control group ( p = 0.06 ). The subgroup of patients with AVM (n: 9), who also underwent DSA, showed a statistically significant difference between the location of the landmarks compared to subjects with no additional imaging: 0.78 mm (95% CI: 0.72–0.84) vs. 0.69 mm (95% CI: 0.66–0.72), p = 0.016 . This is however a minimal difference (0.1 mm) and the mean difference in landmark location for each AVM patient remained submillimeter. This study demonstrates submillimeter stability of the Leksell Frame G in GKR throughout the treatment procedure. PACS number(s): 87.53.‐j, 87.53.Ly, 87.56.Fc